2012
DOI: 10.1093/ndt/gfs386
|View full text |Cite
|
Sign up to set email alerts
|

Reduced survival and quality of life following return to dialysis after transplant failure: the Dialysis Outcomes and Practice Patterns Study

Abstract: TF patients have reduced QOL and higher mortality, particularly due to infections, than TN patients. Interventions to optimize care before and after starting dialysis remain to be identified and applied in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 29 publications
1
74
1
Order By: Relevance
“…Moreover, the risk of sepsis 3-6 months after transplant failure is 3-fold higher than among age-matched dialysis patients with no (20) showed that, compared with transplant-naïve patients, patients with transplant failure were also less likely to use a permanent AV access, particularly within the first 3 months of initiating dialysis. This infection risk is quite concerning, especially because many patients after allograft failure remain on immunosuppression, including prednisone, calcineurin inhibitors, and/or antiproliferatives.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the risk of sepsis 3-6 months after transplant failure is 3-fold higher than among age-matched dialysis patients with no (20) showed that, compared with transplant-naïve patients, patients with transplant failure were also less likely to use a permanent AV access, particularly within the first 3 months of initiating dialysis. This infection risk is quite concerning, especially because many patients after allograft failure remain on immunosuppression, including prednisone, calcineurin inhibitors, and/or antiproliferatives.…”
Section: Discussionmentioning
confidence: 99%
“…The number of dialysis patients with a failed kidney transplant is increasing, and allograft failure among previous recipients of a kidney transplant is now the fourth leading cause of ESRD in the United States [6]. KTRs returning to dialysis have a significantly reduced survival rate compared to both the transplant-naïve dialysis population and those with functioning renal grafts [7][8][9]. Various factors, including age, disease recurrence, human leukocyte antigen (HLA) matching, delayed graft function, and various other donor-related factors that also influence graft survival influence the long-term outcome of kidney transplantation [10].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent analysis from the French Renal Epidemiology and Information Network, utilizing a robust case-control design and accounting for extensive comorbidity and biochemical adjustments between transplant-naïve patients and patients with transplant failure, similarly demonstrated equivalent survival between the two groups (6). By contrast, two analyses, one using data from the Scientific Registry of Transplant Recipients (SRTR) among a United States population and the second from the Dialysis Outcomes and Practice Patterns Study (DOPPS), yielded different results (7,8). Both the SRTR and DOPPS studies restricted comparisons to transplant-naïve dialysis patients who, similar to patients with transplant failure, were potentially transplant eligible by virtue of being placed on a transplant waiting list.…”
mentioning
confidence: 98%
“…The observation that these patients suffer from disproportionately high rates of sepsis and infection-related mortality has led to the hypothesis that a history of prolonged and ongoing exposure to chronic immunosuppression may be mediating these risks (4,8,9). Moreover, the transplanted kidney itself may be an ongoing source of systemic inflammation and hypoalbuminemia even in the absence of overt clinical evidence of rejection (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation